Tourist’s Motivation and Behavioural Intention to Visit a Religious Buddhist Site: A Case Study of Bodhgaya - Piramanayagam, Senthilkumaran (The international journal of religious tourism and pilgrimage, 2021)
The purpose of this study is to identify the motivation factors and investigate their impact on the behavioural intention of pilgrims at Bodhgaya, one of the most prominent Buddhist religious sites in India. To achieve this objective, 28 religious motivational items were identified based on previous studies and subjected to exploratory factor analysis (EFA). The EFA resulted in a three-factor model, which was further tested using confirmatory factor analysis. The identified religious motivational factors were religious belief, service quality and history, architecture and cultural aspects of religious sites. The role of these motivational factors and their influence on behavioural intention was further tested using structural equation modelling. The findings of the study reveal that service quality is a primary motivational factor affecting behavioural intention of religious tourists at Bodhgaya, followed by religious belief. However, history, architecture, and cultural aspects of Bodhgaya had no significant influence on behavioural intention of tourists. The study recommends that service providers at this destination need to pay more attention to enhancing service quality.